Development of Karawo Motif Design System Based on Philosophical Values of Gorontalo Regional Culture - Latief, Mukhlisulfatih; Tuloli, Moh. Syafri (Procedia computer science, 2024)
Karawo is a traditional embroidered cloth for the people of the Gorontalo region. Currently karawo has been widely used by the surrounding community and the outside community in the form of souvenirs or other things. On the one hand, the Gorontalo Region is an area that has many cultures and customs. We need to protect and preserve this culture so that this culture does not quickly become extinct. The lack of karawo motif designs that have a Gorontalo regional cultural philosophy causes karawo craftsmen to lack ideas to design karawo motifs in various design variations. This can be overcome by creating a system that can make several variations of the karawo motif design with the help of computer algorithms. The development of this karawo motif design uses several object or image transformation functions, namely rotation, translation, mirror, flip and zoom functions. To enrich the object so that it looks varied, arithmetic operations and boolean operations are also used to value the color component of each point in the image. The usability measurement results show that the eligibility value of usefulness is 85.71%, ease of use is 100%, ease of learning is 85.71% and satisfaction is 92.86%. The average of all dimensions is 91.07% or it is included in the very satisfied category.